Delivering Integrated Transit, Land Development and Finance – a Guide and Manual: with Application to Trackless Trams. - Mouritz, Mike; Newman, Peter GW; Davies-Slate, Sebastian; Jones, Evan; Hargroves, Karlson; Sharma, Rohit; Adams, David (http://sbenrc.com.au, 2018)
Most cities want more and better public transport along with more lively, productive and sustainable centres, especially in the suburbs. Most cities want to integrate this transit and land-use. But how? This report shows how transit-land development integration has been happening around the world using funding and finance as the glue. This is the core idea of our research on how to procure transit in cities in the 21st century, with a focus on Australian cities and within the context of rapidly changing technology especially the Trackless Tram.